A tradição da folia de reis como manifestação cultural e religiosa no Quilombo Kalunga, Comunidade Areia - Soares, Ozenildo Dias (Universidade Federal do Tocantins, 2023)
The Kalunga people lives in the intersection between the counties of Arraias (TO), Cavalcante (GO), Monte Alegre de Goiás, Paranã (TO) and Teresina de Goiás. In the processes of recognition and demarcation with the Palmares Cultural Foundation and the National Institute for Colonization and Agrarian Reform (INCRA), two separated territories were created: Kalunga and Kalunga do Mimoso. In the quilombo Kalunga, on the limits of the municipality of Monte Alegre de Goiás there is a locality called Fazenda Areia or Comunidade Areia. In it there is a tradition of the Folia de Santos Reis, which has been passed on from generation to generation. I am a Kalunga quilombola, born and raised in Areia, trying to understand better the role and the cultural and religious meanings of this practice, I launch too as a research question: how is the Folia de Santos Reis structured and organized in the Kalunga territory, in the Comunidade Areia? For that, I defined as a general objective to understand the structure and organization of the Folia de Santos Reis in Quilombo Kalunga, Comunidade do Areia. This is an ethnographic research, with reports of memories of the author's experiences and interviews with a semi-structured script, carried out with elders and crones. The development of this work reflects on my perspective of motivating and encouraging future generations not to forget this cultural and religious tradition. The development of this research brought evidence that the Folia de Santos Reis is a cultural and religious manifestation practiced for many generations in the Comunidade Areia. This practice has identity importance and belonging to the Kalunga People.